Representasi Penderitaan Tokoh Alie dalam Novel Rumah untuk Alie - Fatmawati Fatmawati; Aditya Ansor Alsunah; Lina Siti Nurwahidah; Cecep Dudung Julianto (Asosiasi Ide Bahasa Kepri, 2026)
This study aimed to analyze the representation of Alie’s suffering in the novel Rumah untuk Alie through the perspective of literary psychology. The research focused on family pressures as the main factor shaping Alie’s personality and psychological condition. The study employed a qualitative descriptive method with a literary psychology approach, examining the interaction between the character and her social environment. Data were collected through a literature study, including careful reading and documentation of events and dialogues in the novel that illustrate family pressure and its psychological impact. Data analysis was conducted chronologically by identifying forms of family pressure, categorizing them into hatred,, rejection, verbal and physical abuse, and analyzing their influence on Alie’s psychological state and personality development. The results indicated that Alie experienced repeated family pressure in the forms of verbal and physical violence,,, rejection, and neglect. These pressures contributed to feelings of guilt, despair, passivity, and withdrawal, leading to long-term psychological trauma. Monologues and internal dialogues were found to represent her inner conflict and emotional suffering. This study concludes that the representation of Alie’s suffering in the novel illustrates the profound impact of family pressure on the psychological development of the character, highlighting literature’s role as a reflection of human psychological reality.